Efforts To Increase Community Capacity Through Msme Assistance In Ntb Province Post The 2018 Lombok Earthquake Disaster - Supriyanto Darmansyah; Kusuma Kusuma; Sobar Sutisna; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
The earthquake disaster that hit Lombok on August 5 2018 has caused problems in NTB's economic recovery that have not been resolved. As a province highly dependent on the tourism sector, the impact of sluggish tourism due to the earthquake also impacted the weakening of other economic sectors. To overcome this problem, a strategy for the recovery program for UMKM (micro, small and medium enterprises) and IKM (small and medium industries) is taken which is fair, equitable, and on target. This strategy is considered the most effective in creating synergies with other economic sectors, including tourism. The presence of UMKM and IKM is often closely related to the existence of tourism destinations which are the backbone of the NTB economy. This research aims to provide an overview of the distribution and assist community capacity building through MSMEs in NTB to various parties, in order to facilitate the implementation of MSME and IKM recovery programs to revive the economy.